Pengaruh Literasi Asuransi Syari’ah dan Kepercayaan Terhadap Minat Menggunakan Asuransi Syari’ah - A, Alfajri; J, Julina; H, Herlinda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Interest in Sharia Insurance refers to the level of interest and desire of an individual or group to use insurance products and services that are in accordance with Islamic sharia principles. To support the growth of sharia insurance, it is necessary to have public understanding and awareness through sharia insurance literacy, apart from that, individual trust in the right company is also a consideration in attracting customers to use sharia insurance products. This research aims to analyze sharia insurance literacy factors on interest in using sharia insurance. This research was conducted at PT.Takaful general. The population in this research is PT. General takaful for the last 3 years was 110 people. The sampling method in this research is the Random Sampling Method. The data used is primary data and secondary data. Quantitative data analysis method. The research results show that sharia insurance literacy and trust influence interest in using sharia insurance both partially and simultaneously. The results of the Coefficient of Determination (R²) show that the magnitude of the influence of the two dependent variables is 59.4%. Meanwhile, the remaining 40.6% are other variables not examined in this research.